2010
DOI: 10.1152/ajpregu.00275.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dose combinations of exendin-4 and salmon calcitonin produce additive and synergistic reductions in food intake in nonhuman primates

Abstract: Glucagon-like peptide-1 (GLP-1) and amylin mediate the feedback control of eating by seemingly separate, but overlapping mechanisms. This study examined the effects of combined doses of the GLP-1 agonist, exendin-4 (Ex-4), and the amylin analog, salmon calcitonin (sCT), on food intake and meal patterns in adult male rhesus monkeys. Monkeys received intramuscular injections of Ex-4 (0, 0.1, 0.32, or 0.56 microg/kg), sCT (0, 0.1, or 0.32 microg/kg), or combinations thereof before a 6-h daily access to food. Dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…Combined amylin and GLP-1 receptor agonism has also been assessed (Bello et al, 2010). This study evaluated the acute anorexigenic effects of coadministering the amylin/calcitonin receptor agonist salmon calcitonin alone and in combination with GLP-1 receptor agonist exenatide in a non-human primate model.…”
Section: E Amylin and Glucagon-like Peptidementioning
confidence: 99%
“…Combined amylin and GLP-1 receptor agonism has also been assessed (Bello et al, 2010). This study evaluated the acute anorexigenic effects of coadministering the amylin/calcitonin receptor agonist salmon calcitonin alone and in combination with GLP-1 receptor agonist exenatide in a non-human primate model.…”
Section: E Amylin and Glucagon-like Peptidementioning
confidence: 99%
“…In all of these studies, the combination of leptin with amylin, FGF21, or exendin-4 improved weight loss synergistically in diet-induced obese rodents when compared with treatment with the respective monotherapies. Other preclinically evaluated GLP-1-based combination therapies include the salmon calcitonin with exendin-4 (Bello et al, 2010), GLP-1 with PYY (Neary et al, 2005), exenatide with CCK (Trevaskis et al, 2015), and liraglutide with an melanocortin 4 receptor agonist (setmelanotide, RM-493) , which has recently been shown to correct obesity in POMC-deficient humans (Kuhnen et al, 2016). In all of these reports, the combination therapy demonstrated metabolic benefits greater than what can be achieved by the respective hormone monotherapies.…”
Section: B Coadministration Of Single Hormonesmentioning
confidence: 99%
“…Amylin acts centrally to promote negative energy balance (24,50), and several reports have demonstrated that amylin can enhance the anorectic effects of other feeding-related signals in an additive if not synergistic manner (6,10,22,35). Of particular interest is that amylin interacts cooperatively with the adipose-derived hormone leptin to produce enhanced suppression of food intake and body weight (13,15).…”
mentioning
confidence: 99%